2003
DOI: 10.1126/science.1076921
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Transitions from Welfare to Work and the Well-Being of Preschoolers and Adolescents

Abstract: Results from a longitudinal study of 2402 low-income families during the recent unprecedented era of welfare reform suggest that mothers' transitions off welfare and into employment are not associated with negative outcomes for preschoolers (ages 2 to 4 years) or young adolescents (ages 10 to 14 years). Indeed, no significant associations with mothers' welfare and employment transitions were found for preschoolers, and the dominant pattern was also of few statistically significant associations for adolescents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
171
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(180 citation statements)
references
References 12 publications
(11 reference statements)
7
171
2
Order By: Relevance
“…Thus, child age may serve as a moderator of the link between welfare and work experiences and family processes. For example, Chase-Lansdale et al (2003) reported that low-income mothers' movements into employment following welfare reform predicted decreases in time spent with young children, but little change in time spent with adolescents, who are in school and other activities much of the day regardless of parental work behavior. As another example, young children's need for alternate care arrangements may increase the financial demands for families moving into employment, hence exacerbating links between new employment and financial strain for families of younger versus older children.…”
Section: Effects Of Child Agementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, child age may serve as a moderator of the link between welfare and work experiences and family processes. For example, Chase-Lansdale et al (2003) reported that low-income mothers' movements into employment following welfare reform predicted decreases in time spent with young children, but little change in time spent with adolescents, who are in school and other activities much of the day regardless of parental work behavior. As another example, young children's need for alternate care arrangements may increase the financial demands for families moving into employment, hence exacerbating links between new employment and financial strain for families of younger versus older children.…”
Section: Effects Of Child Agementioning
confidence: 99%
“…In a demographic overview, Bianchi (2000) found that dramatic increases in maternal employment over the past decades have not brought with them substantial decreases in the time mothers spend with their children. Because employed mothers tend to spend less time in leisure and other non-child activities, they compensate for time away from their children due to work (Chase-Lansdale et al, 2003). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been used in the Head Start Family and Child Experiences Survey and in the Abecedarian study. It has also been used in studies of the effect of maternal employment on children's educational outcomes (Chase-Lansdale et al, 2003). We specifically chose subtests that are thought to be appropriate for relatively young children, including pre-K children (Mather & Woodcock, 2001): Letter-Word Identification, Spelling, and Applied Problems.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the reported research in the literature focuses on the benefits of working mothers [6]. Galinsky [7] found that 81% of 13-18 year olds believed working mothers can have as good a relationship with their children as do stay-at-home mothers.…”
Section: Introductionmentioning
confidence: 99%